Deficiency of NOD1 Improves the β-Adrenergic Modulation of Ca2+ Handling in a Mouse Model of Heart Failure - Val-Blasco, Almudena; Navarro-García, Jose A.; Tamayo, Maria; Piedras, Maria J.; Prieto, Patricia; Delgado, Carmen; Ruiz-Hurtado, Gema; Rozas-Romero, Laura; Gil-Fernández, Marta; Zaragoza, Carlos; Boscá, Lisardo; Fernández-Velasco, María (Frontiers in Physiology, 2018)
Heart failure (HF) is a complex syndrome characterized by cardiac dysfunction, Ca2+ mishandling and chronic activation of the innate immune system. Reduced cardiac output in HF leads to compensatory mechanisms via activation of the adrenergic nervous system. In turn, chronic adrenergic overstimulation induces pro-arrhythmic events, increasing the rate of sudden death in failing patients. Nucleotide-binding oligomerization domain-containing protein 1 (NOD1) is an innate immune modulator that plays a key role in HF progression. NOD1 deficiency in mice prevents Ca2+ mishandling in HF under basal conditions, but its role during β-adrenergic stimulation remains unknown. Here, we evaluated whether NOD1 regulates the β-adrenergic modulation of Ca2+ signaling in HF. Ca2+ dynamics were examined before and after isoproterenol perfusion in cardiomyocytes isolated from healthy and from post-myocardial infarction (PMI) wild-type (WT) and Nod1–/– mice. Isoproterenol administration induced similar effects on intracellular [Ca2+]i transients, cell contraction and sarcoplasmic reticulum (SR)-Ca2+ load in healthy WT and Nod1–/– cells. However, compared with WT-PMI cells, isoproterenol exposure induced a significant increase in the [Ca2+]i transients and cell contraction parameters in Nod1–/–-PMI cells, which mainly due to an increase in SR-Ca2+ load. NOD1 deficiency also prevented the increase in diastolic Ca2+ leak (Ca2+ waves) induced by isoproterenol in PMI cells. mRNA levels of β1 and β2 adrenergic receptors were significantly higher in Nod1–/–-PMI hearts vs WT-PMI hearts. Healthy cardiomyocytes pre-treated with the selective agonist of NOD1, iE-DAP and perfused with isoproterenol showed diminished [Ca2+]i transients amplitude, cell contraction and SR-Ca2+ load compared with vehicle-treated cells. iE-DAP-treated cells also presented increased diastolic Ca2+ leak under β-adrenergic stimulation. The selectivity of iE-DAP on Ca2+ handling was validated by pre-treatment with the inactive analogue of NOD1, iE-Lys. Overall, our data establish that NOD1 deficiency improves the β-adrenergic modulation of Ca2+ handling in failing hearts.